2018
DOI: 10.20996/1819-6446-2018-14-3-319-323
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Properties of Lisinopril: New Possibilities

Abstract: Первый Московский государственный медицинский университет им. И.М. Сеченова (Сеченовский Университет) Россия, 119991, Москва, ул. Трубецкая, 8 стр. 2 Цель. Изучить изменения жесткости сосудистой стенки, сосудодвигательной функции эндотелия и появления новых случаев фибрилляции предсердий (ФП) у больных артериальной гипертензией (АГ) при длительном лечении лизиноприлом. Материал и методы. В исследование включено 66 больных АГ с синусовым ритмом в возрасте от 48 до 64 лет (средний возраст 58,4±4,2 лет). Пацие… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Cardiomyocytes will be treated with an ACE inhibitor; an ARB; a combination of the two, whose efficacy is debated in clinical practice; or a control saline solution. The ACE inhibitor lisinopril and the ARB candesartan will be used in the study because both medications are commonly prescribed and have shown promise in cardiac studies unrelated to hypertension [24][25][26][27]. Since no prior studies have shown their effects on individual cardiomyocytes, this study will use 1 and 10µM dosages to determine whether a higher dose yields greater effects, and future studies can use these results to find dosages which are effective and clinically applicable.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiomyocytes will be treated with an ACE inhibitor; an ARB; a combination of the two, whose efficacy is debated in clinical practice; or a control saline solution. The ACE inhibitor lisinopril and the ARB candesartan will be used in the study because both medications are commonly prescribed and have shown promise in cardiac studies unrelated to hypertension [24][25][26][27]. Since no prior studies have shown their effects on individual cardiomyocytes, this study will use 1 and 10µM dosages to determine whether a higher dose yields greater effects, and future studies can use these results to find dosages which are effective and clinically applicable.…”
Section: Methodsmentioning
confidence: 99%
“…Фармакодинамические преимущества лизиноприла связываются с его комплексным вазодилататорным, диуретическим и симпатолитическим воздействием, гидрофильностью и возможностью применения у тучных больных, с прямой, длительной, независимой от печеночного метаболизма фармакоактивностью с меньшим риском лекарственной асинергии [6]. Последнее выгодно отличает лизиноприл и ставит его вне конкуренции с остальными ингибиторами АПФ, имеющими пролекарственную форму, требующую первичной метаболической активации в печени [7,8].…”
Section: Fixed Dose Combination In Hypertensive Patientsunclassified